The effects of different leaves on microflora, phytochemistry and its sensory acceptability of gulai tempoyak paste - Abdul Aris, Mohd Hafiz (2015)
Antimicrobial activity of Vietnamese coriander, turmeric, and asam gelugor leaves were determined via in vitro using agar well diffusion test and minimum inhibitory concentration (MIC). The leaves of these plants have continuously applied in the food system, and in this case, gulai tempoyak paste (GTP) had been chosen as the food subject to evaluate the effectiveness of these leaves in controlling microbial growth through the study of storage condition. Apart from that, the phytochemistry and the sensory properties of GTP were determined to identify the differences between nil addition of plant leaves (control sample) and with addition of Vietnamese coriander, turmeric, and asam gelugor leaves. Based on agar well diffusion test result, a concentration of 2 mg/mL of Vietnamese coriander leaves extract in distilled water showed strong antibacterial effect with (17.20 ± 5.42 mm) at inhibition zone. As for antifungal activity, extract of turmeric leaves in distilled water resulted strong activity (15.13 ± 0.17 mm) at inhibition zone compared to other solvents. Meanwhile, as for MIC, 2 mg/mL was the lowest concentration needed from all extracts of leaves to inhibit growth of microbial, as shown in Vietnamese coriander, turmeric, and asam gelugor leaves extracts towards selected spoilage microorganisms. On the other hand, GTP without addition of leaves was treated as control and all the prepared GTPs were stored at 30 °C for 2 days before analyses had been carried out using total plate count (TPC) and yeast and mould count (YMC). The addition of asam gelugor leaves to GTP for 5 minutes of the cooking period significantly (p<0.05) reduced TPC (log10 3.54 CFU/g) compared to Vietnamese coriander (log10 4.67 CFU/g) and turmeric leaves (log10 4.70 CFU/g). Apart from that, this study also demonstrated that TPC and YMC for GTP with plant leaves reduced significantly within 14 days when stored at 4 ºC, and up to 8 days when stored at 30 ºC, thus, emphasize the microbiological evaluation of GTP. Moreover, the phytochemistry properties of the GTP samples demonstrated significant differences (p<0.05) in pH, moisture, ash, crude fat, crude fibre and carbohydrate between the control sample and the treated samples. Higher level of crude fibre content was demonstrated in GTP added with Vietnamese coriander (4.42 ± 0.23%). Based on sensory evaluation test, the addition of plant leaves slightly affected the acceptability of eating and the physical quality scores of GTP. Nevertheless, there was insignificant difference (p>0.05) in colour, viscosity/consistency, spiciness, and aftertaste. GTP added with Vietnamese coriander leaves resulted in better aroma mean score, and at once produced significantly higher result for overall acceptability. In conclusion, these three types of plant leaves exhibited antimicrobial activity of against selected spoilage bacteria and the addition of plant leaves in GTP possibly improved the microbial safety by inhibiting microbial growth. Furthermore, there were significant effects on microbiological safety of GTP when added with Vietnamese coriander, turmeric, and asam gelugor leaves at different exposure time based on TPC and YMC. Besides, the phytochemistry and the sensory properties of the GTP samples with addition of plant leaves also improved in terms of crude fibre content as well as enhanced sensory attributes for colour, aroma, taste, and overall acceptability of the product.